2014
DOI: 10.2174/1874070701408010006
|View full text |Cite
|
Sign up to set email alerts
|

Mating Types Analysis of Magnaporthe oryzae Populations by Molecular Methods

Abstract: Rice blast is a devastating disease which is caused by the heterothallic fungus Magnaporthe oryzae. Compatible sexual recombination which occurs between two M. oryzae strains of different mating types, can enhance genetic variability. Assessment of mating type alleles is used as a marker to measure population diversity. Forty six isolates of M. oryzae were collected from infected rice leaves from various ecosystems of coastal Odisha, India, and the mating type analysis using molecular markers was carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Also, MAT1‐1 and MAT1‐2 were observed in rain‐fed as well as irrigated fields. The invasive manner of the fungus can be explained through the fact that in the irrigated ecosystem, both mating types are present inside one field which is in agreement with our findings (Samanta et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Also, MAT1‐1 and MAT1‐2 were observed in rain‐fed as well as irrigated fields. The invasive manner of the fungus can be explained through the fact that in the irrigated ecosystem, both mating types are present inside one field which is in agreement with our findings (Samanta et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Nearly all rice blast isolates in the field are males and thus are unable to cross with one another, however many isolates from other grasses are hermaphrodites (Bonman, 1992), therefore it is a possibility that the isolates from rice and from other grasses can cross and produce fertile strains. These fertile strains can enhance the genotypic variability of M. oryzae populations where the progenies may have new capabilities to infect different rice cultivars (Samanta et al, 2014).…”
Section: Biology Of Rice Blast Pathogenmentioning
confidence: 99%
“…The presence of MAT1 ‐ 2 allele in the population at a higher rate (>90%) was also reported by Tansian and Parinthawong (2018) in Thai isolates. Samanta et al (2014) reported the occurrence of MAT1 ‐ 2 population in the uplands and irrigated ecosystems of Central India, and they also reported the occurrence of both mating types in the irrigated ecosystem. A higher MAT1‐2 mating type distribution was also reported from North‐East and Eastern India (Imam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%